PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN KARAKTER PEDULI SOSIAL SISWA - Zakiyah BZ; Halima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in helping to foster the character of social care in students at Madrasah Aliyah Zainul Anwar. This research uses a qualitative approach with a case study type. Data were obtained from observations and interviews with madrasah heads, PAI teachers, and students in grades X and XI who were deliberately selected. The results of the study showed an increase in empathy, cooperation, and solidarity between students. Students began to show initiatives to help friends who were experiencing difficulties, were active in mutual cooperation and community service activities, and were more responsible for the cleanliness and order of the school environment. This success is supported by the example of teachers (uswah hasanah), habituation of social values, and the application of contextual, interactive, participatory, and hands-on experience-based learning approaches. Thus, it can be concluded that the integration of social care values in the learning process and school culture is consistently able to form a more empathetic, cooperative, and responsible student character, as well as create a harmonious school environment with a strong social culture.